A comparative study of endoscopic endonasal dacrocystorhinostomy with and without prolene stenting - Polisetti, Ravibabu; Lanke, Sowmya; Chiniga, Venkateswara Rao (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Dacrocystorhinostomy is the standard treatment for nasolacrimal duct obstruction. Incision was given at the fronto-nasal process of maxilla and flap was elevated by endonasal approach. Lacrimal bone is removed with Kerrison”s punch, lacrimal sac was identified and clear fluid was released. Intubating the nasolacrimal system during dacryocystorhinostomy (DCR) could prevent osteotomy closure and scarring. Outcomes of endoscopic En DCR with and without prolene stenting. Methods: All patients with NLD obstruction who have recurrent watering of eyes or dacryocystitis. The study included patients of either sex who had symptoms and signs suggestive of chronic dacryocystitis. It includes a total of 50 patients. There were 21 males and 29 females. Results: Canalicular irrigation or sac syringing provides essential information about the location of obstruction. Post operatively lacrimal syringing is performed to confirm the patency of the nasolacrimal fistula by directly visualising the flow of saline from rhinostomy opening using nasal endoscopy. In group A syringing was patent in 92% and non patent in 8%. In group B patients syringing was patent in 88% and non patent in 12%. Conclusions: In this study we compared endonasal DCR outcomes with and without stents in 50 cases of Chronic Dacryocystitis in which prolene was used as a stent in 50% of the randomly divided cases. Based on available data and from literature, we conclude that En DCR is safe and simple.